Struggle for fair oil royalties in Sabah: the dynamics of federal-state government relations in Malaysia 2003-2018 - Padlee, Siti Fahlizah binti; Hj Hamil, Jamaie bin; Yaakop, Mohd Rizal Mohd (Department of Government Studies Universitas Muhammadiyah Makassar, 2025)
This study investigates the dynamics of federal-state relations in Malaysia, specifically focusing on Sabah’s efforts to secure increased oil royalties from 2003 to 2018, particularly during the tenure of Chief Minister Musa Aman. Despite the political alignment between the federal government and the Barisan Nasional led state government of Sabah, attempts to raise the oil royalty rate from five percent to 20 percent were ultimately unsuccessful. Employing a qualitative methodology, this research incorporates interviews, official documents, and legislative records, and augments these findings with quantitative data regarding oil production, revenue trends, and socioeconomic indicators. This comprehensive approach assesses the broader implications of the royalty dispute on Sabah’s development. The findings reveal that factors such as federal dominance, institutional constraints, and historical agreements continue to restrict Sabah’s fiscal autonomy. Notably, despite being the largest oil-producing state in Malaysia, Sabah remains the poorest state, underscoring the disconnection between resource generation and regional development. By contextualizing Sabah’s experience within both global and national frameworks, and drawing comparative insights from other oil-producing federal states, including Nigeria, Canada, and Brazil, this study emphasizes how centralized control over oil revenues, coupled with political and constitutional inflexibility, can hinder equitable development. The article advocates for more inclusive federal-state negotiations and encourages a reevaluation of resource sharing mechanisms within Malaysia’s federal system.